Model Pembelajaran PAI Berbasis Neurosains : Inquiry Learning - Reni Dianti Rukmini; Sutarto Sutarto; Dewi Purnama Sari; Aida Rahmi Nasution (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research discusses the neuroscience-based PAI learning model with the concept of the inquiry learning model. The aim of this research is to find out how the neuroscience-based PAI learning model uses the concept of the inquiry learning model. This type of research is library research. The data sources used in this research are primary sources and secondary sources. The primary data source in this research is a journal that discusses neuroscience-based PAI learning models and inquiry learning models, while secondary data sources consist of relevant journals and books. The results of the research show that Neuroscience is very appropriate to use in learning. All human potential is based on the brain or mind, therefore, in studying Islamic religious education, it is also necessary to collaborate with Neuroscience, so that the optimization of students' brain potential is achieved, because it is the only science that studies the brain or mind is Neuroscience.